Access to Nectin Favors Herpes Simplex Virus Infection at the Apical Surface of Polarized Human Epithelial Cells - Galen, Benjamin (American Society for Microbiology, 2006)
Viral entry may preferentially occur at the apical or the basolateral surfaces of polarized cells, and differences may impact pathogenesis, preventative strategies, and successful implementation of viral vectors for gene therapy. The objective of these studies was to examine the polarity of herpes simplex virus (HSV) entry using several different human epithelial cell lines. Human uterine (ECC-1), colonic (CaCo-2), and retinal pigment (ARPE-19) epithelial cells were grown on collagen-coated inserts, and the polarity was monitored by measuring the transepithelial cell resistance. Controls were CaSki cells, a human cervical cell line that does not polarize in vitro. The polarized cells, but not CaSki cells, were 16- to 50-fold more susceptible to HSV infection at the apical surface than at the basolateral surface. Disruption of the tight junctions by treatment with EGTA overcame the restriction on basolateral infection but had no impact on apical infection. No differences in binding at the two surfaces were observed. Confocal microscopy demonstrated that nectin-1, the major coreceptor for HSV entry, sorted preferentially to the apical surface, overlapping with adherens and tight junction proteins. Transfection with small interfering RNA specific for nectin-1 resulted in a significant reduction in susceptibility to HSV at the apical surface but had little impact on basolateral infection. Infection from the apical but not the basolateral surface triggered focal adhesion kinase phosphorylation and led to nuclear transport of viral capsids and viral gene expression. These studies indicate that access to nectin-1 contributes to preferential apical infection of these human epithelial cells by HSV.